An Observational Study of Cerebral Blood Flow Velocity During Hypotensive Epidural Anesthesia. Issue 6 (December 2016) - Bombardieri, Anna Maria; Sharrock, Nigel E.; Ma, Yan; Go, George; Drummond, John C.
Abstract : (Abstracted from Anesth Analg, 122:234–242, 2016) Sympathetic blockade has been used as a means to achieve mean arterial blood pressure (MAP) of less than 50 mm Hg while administering epinephrine by infusion to support circulation. Adequate cerebral blood flow (CBF) appears to have been accomplished in such cases, leading researchers to conclude that there is no association between hypotensive epidural anesthesia (HEA) administration and gross adverse effects on either neurological outcome or cognitive function.